Effect of overweight/obesity and metabolic syndrome on frailty in middle‐aged and older Japanese adults - Yuki Nishida; Yosuke Yamada; Satoshi Sasaki; Eiichiro Kanda; Yoshihiko Kanno; Tatsuhiko Anzai; Kunihiko Takahashi; Keita Yamauchi; Fuminori Katsukawa (Wiley, 2024)
Abstract Background The potential for developing frailty exists in middle‐aged and older adults. While obesity and metabolic syndrome (MetS) increase the risk of frailty in older adults, this relationship remains unclear in middle‐aged adults, who are prone to developing lifestyle‐related diseases. Objective To examine the effect of overweight/obesity and MetS on frailty development in middle‐aged and older Japanese adults using real‐world data. Methods This nationwide cohort study used exhaustive health insurance claims data of 3,958,708 Japanese people from 2015 to 2019 provided by the Japan Health Insurance Association. Participants aged ≥35 and < 70 years who received health checkups in 2015 were included. Multivariate logistic regression was used to assess the effect of body mass index (BMI) and MetS or MetS components (i.e., diabetes, hypertension, and dyslipidemia) in 2015 on frailty risk assessed using the hospital frailty risk score in 2019. Additionally, a subgroup analysis was performed to examine the interaction effects of MetS components and 4‐year weight change (%) on frailty risk among participants who were overweight and obese (BMI ≥25 kg/m2). Results In 2019, 7204 (0.2%) and 253,671 (6.4%) participants were at high and intermediate frailty risks, respectively. Obesity and MetS were independently associated with intermediate/high frailty risk (odds ratio (OR) 1.36, p < 0.05; OR 1.23, p < 0.05, respectively) and high frailty risk (OR 1.80, p < 0.05; OR 1.37, p < 0.05, respectively) in all participants. Although all MetS components were frailty risk factors, these effects diminished with age in both sexes. Subgroup analysis of patients with diabetes revealed that 5%-10% weight loss was associated with reduced frailty risk in both sexes. Conclusions Obesity, MetS, and MetS components were independent frailty risk factors in middle‐aged and older Japanese adults. Weight loss of up to 10% over 4 years prevented frailty in patients with diabetes who were overweight and obese.